Determinan Peringkat Obligasi Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Adhitya Bayu Suryantara; Muhammad Habib Husnan; Akram Akram (The Indonesia Capital Market Institute, 2022)
This study aims to determine the factors that influence bank bond ratings, specifically investigating the effect of leverage, liquidity, profitability, activity, bond maturity, bond guarantees, good corporate governance ratings, and underwriting securities on banking bond ratings. This study is an associative study using ordinal logistic regression analysis with the help of SPSS 16. The population in this study were banking companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019 and ranked by Pefindo. The sample was determined based on the purposive sampling method to obtain 11 sample companies. The independent variable data used in this study are secondary data obtained from the Indonesia Stock Exchange (IDX) and the Indonesian Institute for Corporate Governance (IICG). Meanwhile, bond rating data was obtained from Pefindo. The results show that leverage has a significant negative effect on bond ratings. Liquidity does not affect bond ratings. Profitability has a positive effect on bond ratings. Activity has a significant positive effect on bond ratings. Bond maturity has no significant effect on bond ratings. Bond guarantees have a significant positive effect on bond ratings, and good corporate governance ratings have a significant positive effect on bond ratings. Meanwhile, the underwriter does not affect the bond rating.